Exercise barriers and facilitators during hematopoietic stem cell transplantation: a qualitative study - Kerry Courneya; Mi-Seong Yu; Ki-Yong An; Jiyong Byeon; Meeok CHOI; June-Won Cheong; Justin Y Jeon (BMJ Open)
Objective Although exercise is beneficial in patients undergoing hematopoietic stem cell transplantation (HSCT), motivating patients to exercise is challenging. We aimed to understand exercise barriers and facilitators during HSCT treatment while participating in a daily unsupervised exercise programme.Participants Patients scheduled to have HSCT.Study design 6 participants were included in this descriptive qualitative study during HSCT treatment while participating in an exercise programme to identify perceived barriers and facilitators of the exercise. An average of three semi-structured interviews were conducted per patient.Setting Exercise during HSCT treatment in an isolated immune room.Intervention Daily unsupervised exercise.Results A total of six patients completed a 6-week exercise programme as well as all scheduled interviews, whose compliance to the exercise programme ranged from 12% to 79%. Based on interview results, three themes were identified as barriers to exercise and four themes were identified as facilitators to exercise. Patients experienced physical and psychological barriers such as nausea, vomiting, sore throat, reduced appetite, decreased willpower and anxiety due to feelings of isolation. Environmental factors included negative opinions about exercise programmes and lack of encouragement from the haematologist. Facilitators of exercise included willpower, easy and simple exercise, convincing explanations from haematologists and supervised support from exercise specialists.Conclusion Our study has identified potential barriers and facilitators associated with exercise participation during HSCT. Supervised exercise recommended by a haematologist, convincing explanation on the benefit of exercise by medical personnel, positive feedback from other HSCT survivors and supervision by exercise specialists may increase compliance to the exercise programme during HSCT.Trial registration number ISRCTN61498391.